Alcohol, psychiatry and society Comparative and transnational perspectives, 1700-1990s - Ernst, Waltraud; Müller, Thomas (Manchester University Press, 2022)
The medicalisation of alcohol use has become a prominent discourse that guides policy makers and impacts public perceptions of alcohol and drinking. This book maps the historical and cultural dimensions of the phenomenon. Emphasising medical attitudes and theories regarding alcohol and the changing perception of alcohol consumption in psychiatry and mental health, it explores the shift from the use of alcohol in clinical treatment and as part of dietary regimens to the emergence of alcoholism as a disease category that requires medical intervention and is considered a threat to public health.